Pengaruh Tingkat Pemahaman, Sikap Dan Motivasi Terhadap Minat Mahasiswa Akuntansi Untuk Mengambil Sertifikasi Chartered Accountant (CA) - Virgantini, Pande Kadek Nita; Indraswarawati, Sang Ayu Putu Arie; Yuniasih, Ni Wayan (UNHI Press, 2025)
This research aims to examine and analyze the influence of the level of understanding about Chartered Accountants (CA), attitudes regarding Chartered Accountants (CA) and motivation to obtain a Chartered Accountant (CA) on students' interest in taking the Chartered Accountant (CA) profession at the Indonesian Hindu University. This research approach uses a quantitative approach. This research uses primary data where data is collected using a questionnaire. This research was conducted at the Accounting Study Program, Faculty of Business Economics and Tourism with a population of 469 and a sample size of 82, using simple random sampling techniques and Slovin formula calculations. The data analysis technique in this research uses descriptive statistics, classical assumption testing, multiple linear regression analysis, hypothesis testing and coefficient of determination testing. The results of the analysis prove that simultaneously the level of understanding about Chartered Accountants (CA), attitudes about Chartered Accountants (CA) and motivation to get a Chartered Accountant (CA) influence students' interest in taking Chartered Accountant certification.